Algoritmos diagnósticos en el manejo de la hidronefrosis obstructiva y no obstructiva. - Corral Rosillo, J.; Delgado Martín, J.A.; Fuentes Márquez, I.; Resel, Luis; San José Mansó, L.; Gómez Vegas, Ángel; Silmi Moyano, A.; Blázquez Izquierdo, J. (Clínicas Urológicas de la Complutense, 2002)
Sin resumen